2008
DOI: 10.5027/andgeov35n2-a03
|View full text |Cite
|
Sign up to set email alerts
|

Deformacion compresiva cuaternaria en la Cordillera Principal de Chile central (Cajon del Maipo, este de Santiago).Quaternary compressional deformation in the Main Cordillera of Central Chile (Cajon del Maipo, east of Santiago).

Abstract: El estudio geológico y estructural detallado de sedimentos recientes en el valle del río Maipo (Cajón del Maipo), al este de Santiago, muestra la existencia de una deformación en compresión con fallas inversas y pliegues de arrastre contemporáneos. Estas estructuras son cinemáticamente compatibles con una dirección de esfuerzo cercana a N-S (N338°E) que afecta también a las unidades de roca más antiguas (Formación Abanico), que constituyen el sustrato de las terrazas aluviales cuaternarias. En estas rocas del … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…3A). Neotectonic activity of arc-oblique structures within the study area has been demonstrated by Lavenu and Cembrano (2008). They showed that Quaternary terraces of the Maipo river have been faulted and folded by NE and WNW-striking reverse faults, parallel to the trend of regional-scale faults recognized by this study (Fig.…”
Section: Fault Intersections Damage and Permeabilitysupporting
confidence: 76%
“…3A). Neotectonic activity of arc-oblique structures within the study area has been demonstrated by Lavenu and Cembrano (2008). They showed that Quaternary terraces of the Maipo river have been faulted and folded by NE and WNW-striking reverse faults, parallel to the trend of regional-scale faults recognized by this study (Fig.…”
Section: Fault Intersections Damage and Permeabilitysupporting
confidence: 76%
“…Focal mechanisms indicate normal movement of the SW-dipping Pichilemu fault (Farías et al, 2011;Aron et al, 2013), consistent with the expected relaxation of NWstriking crustal faults (normally under compression) during the co-and post-seismic periods, as was also observed in the volcanic arc at the Main Cordillera (Spagnotto et al, 2015). In the Main Cordillera, there is no direct evidence of neotectonic activity of the PFS, but similar, WNW-striking faults have been shown to displace Quaternary terraces of the Maipo River, ∼ 25 km to the north of the PFS (Lavenu and Cembrano, 2008). One of the focal mechanism solutions of the Las Melosas earthquake, a major (M w 6.9) intraplate seismic event registered in 1958 in the Main Cordillera, less than 10 km to the north of the PFS, is compatible with activity along a WNW-striking fault (Alvarado et al, 2009).…”
Section: Beyond the Pfs: The Maipo Deformation Zonesupporting
confidence: 71%
“…The strike of individual veins varies from ENE to WNW, but the whole vein system defines a WNW-trending belt, 1.5 km long and 200 m wide. The veins are composed of quartz, calcite and barite with a sulfide ore of galena, sphalerite, tennantite/tetrahedrite, chalcopyrite and bornite (Leal, 2019), and they are syn-tectonic, as demonstrated by several pieces of evidence of hydrothermal mineral crystallization during fault slip (Fig. 4).…”
Section: Structural Settingmentioning
confidence: 99%